Quotidienneté et résistance - HATEM, Jad (Studia Universitatis Babeș-Bolyai Philosophia, 2024)
Daily Life and Resistance. Between daring project and tranquility, everyday life chooses the second term, the first threatening the habituality of serene existence. To do this, it deploys a minimal morality and, above all, a structure of resistance. The study is based on Andrei Pleşu, Simone de Beauvoir, and Josep Maria Esquirol. RÉSUMÉ. Entre projet audacieux et quiétude, la quotidienneté choisit le second terme, le premier menaçant l’habitualité de l’existence sereine. Il déploie pour cela une morale minimale et surtout une structure de résistance. L’étude se base sur Andrei Pleșu, Simone de Beauvoir et surtout Josep Maria Esquirol. Mots-clef : Vie quotidienne – Résistance - minima moralia - cultiver son jardin - Disponibilité